Expectation Calculation and Macroeconomic Dynamics - Evans, George W.; Ramey, Garey (American Economic Review, 1992)
We establish a framework wherein agents make expectation-revision decisions subject to a specified calculation technology and preferences over forecast errors. The technology endows agents with correctly specified economic models, but the cost of expectation calculation using these models leads to gradual and incomplete adjustment to long-run rational-expectations equilibrium. The rational-expectations hypothesis emerges as a special case of the equilibrium paths obtained in our framework. In a natural-rate model of monetary policy, calculation technology gives rise to long-run nonneutrality and hysteresis effects, and incomplete adjustment of forecast rules causes output fluctuations to be amplified.